Ecological networks and urban crime: the structure of shared routine activity locations and neighborhood-level informal control capacity - Browning, Christopher R. (Criminology, 2017)
By drawing on the work of Jacobs (1961), we hypothesize that public contact among neighborhood residents while engaged in day‐to‐day routines, captured by the aggregate network structure of shared local exposure, is consequential for crime. Neighborhoods in which residents come into contact more extensively in the course of conventional routines will exhibit higher levels of public familiarity, trust, and collective efficacy with implications for the informal social control of crime. We employ the concept of ecological (“eco‐”) networks—networks linking households within neighborhoods through shared activity locations—to formalize the notion of overlapping routines. By using microsimulations of household travel patterns to construct census tract‐level eco‐networks for Columbus, OH, we examine the hypothesis that eco‐network intensity (the probability that households tied through one location in a neighborhood eco‐network will also be tied through another visited location) is negatively associated with tract‐level crime rates (N = 192). Fitted spatial autoregressive models offer evidence that neighborhoods with higher intensity eco‐networks exhibit lower levels of violent and property crime. In contrast, a higher prevalence of nonresident visitors to a given tract is positively associated with property crime. The results of these analyses hold the potential to enrich insight into the ecological processes that shape variation in neighborhood crime.